2023
DOI: 10.3389/fendo.2023.1119553
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of melatonin against the toxic effects of environmental pollutants and heavy metals on testicular tissue: A systematic review and meta-analysis of animal studies

Abstract: BackgroundEnvironmental pollution and infertility are two modern global challenges that agonize personal and public health. The causal relationship between these two deserves scientific efforts to intervene. It is believed that melatonin maintains antioxidant properties and may be utilized to protect the testicular tissue from oxidant effects caused by toxic materials.MethodsA systematic literature search was conducted in PubMed, Scopus, and Web of Science to identify the animal trial studies that evaluated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 95 publications
(150 reference statements)
4
10
0
Order By: Relevance
“…In the current meta-analysis, melatonin restored testicular injuries caused by radiotherapy and chemotherapy, which was indicated by increased spermatogonia and sperm count, normal morphology, motility, and viability, testis and epididymal weight, and seminiferous tubular height and diameter. These results agree with our previous meta-analyses, which revealed the beneficial impact of melatonin on testicular injuries induced by metabolic disorders, physical and toxic chemical triggers in animal models ( 70 72 ). Radio- and chemotherapy can cause disturbances in spermatogenesis through different mechanisms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current meta-analysis, melatonin restored testicular injuries caused by radiotherapy and chemotherapy, which was indicated by increased spermatogonia and sperm count, normal morphology, motility, and viability, testis and epididymal weight, and seminiferous tubular height and diameter. These results agree with our previous meta-analyses, which revealed the beneficial impact of melatonin on testicular injuries induced by metabolic disorders, physical and toxic chemical triggers in animal models ( 70 72 ). Radio- and chemotherapy can cause disturbances in spermatogenesis through different mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…Melatonin administration elevated animal testosterone and reduced FSH levels in this meta-analysis. According to our recent meta-analysis, melatonin increases testosterone levels but does not affect FSH in rodents with toxin-induced testicular injuries ( 70 ). The existing body of research suggests that melatonin can inhibit the biosynthesis of FSH by decreasing the secretion of gonadotropin-releasing hormone (GnRH).…”
Section: Discussionmentioning
confidence: 98%
“…Melatonin can not only directly clear hydroxyl radical and peroxyhydroxyl radical in vitro and vivo, but also increase antioxidant enzyme activity, such as SOD and GSH‐Px, through MT1 and MT2 receptors to reduce oxidative stress levels 27,28 . A previous study has reported that melatonin alleviated growth retardation induced by deoxynivalenol, nicotine, and ochratoxin A 29‐31 . Consistent with the previous study, our study showed that dietary supplementation with 2 mg kg −1 melatonin significantly increased ADG and feed conversion rate, and melatonin also relieved diquat‐caused weight loss, which indicated that dietary supplementation with 2 mg kg −1 melatonin may be also an effective way to alleviate diquat‐induced growth retardation in piglets.…”
Section: Discussionsupporting
confidence: 90%
“…27,28 A previous study has reported that melatonin alleviated growth retardation induced by deoxynivalenol, nicotine, and ochratoxin A. [29][30][31] Consistent with the previous study, our study showed that dietary supplementation with 2 mg kg −1 melatonin significantly increased ADG and feed conversion rate, and melatonin also relieved diquat-caused weight loss, which indicated that dietary supplementation with 2 mg kg −1 melatonin may be also an effective way to alleviate diquat-induced growth retardation in piglets. Intestinal epithelial barrier function is the key to maintaining intestinal homeostasis.…”
Section: Discussionsupporting
confidence: 90%
“…These results agree with studies on Shetland ponies (Deichsel et al., 2008) and Andalusian stallions (Ruiz et al., 2021). Other studies have observed an increase in the percentage of abnormal sperm in conditions of hypoxia, where the predominant anomalies are head malformations, unlike tail anomalies that are more frequent in normal conditions (Dehdari et al., 2023). Exogenous antioxidants function as electron donors, avoiding an oxide‐reduction chain sacrificing their own molecular integrity, through three levels of protection: Prevention: consists of the formation of ROS above normal levels of the organism.…”
Section: Discussionmentioning
confidence: 90%